Searching for Control: Redefining Asylum-Seeking in the Security Era - Kenyon, Emma (Université d'Ottawa | University of Ottawa, 2012)
Widely considered one of the most generous refugee-receiving countries in the developed world, Canada has embarked on a mission to drastically, and quietly, overhaul its refugee protection regime. Using the language of security and safety, Canada is redefining the motivations and consequences of asylum-seeking as criminal and potentially terrorist actions. By generating expansive immigration legislation and utilizing a range of domestic and international security forces against border intrusion, Canada is succeeding in limiting the number of people to whom it owes protection under international law. This paper argues that these methods are part of an effort by the security regime to expand its influence, and that without transparency and public discussion, the refugee regime in Canada will be effectively dismantled.